Penerapan Metode Vigenere Chiper untuk Mengamankan Data Text - Dicky Arfandy; Magdalena Simanjuntak; Tio Pasaribu (Yayasan Kita Menulis, 2022)
The development of technology in security systems to ensure the confidentiality of data information has grown rapidly. In maintaining the confidentiality of data information, there are sciences in development such as steganography and cryptography. Data and information security is very important in the current reform era. Generally, every institution has important and confidential documents that can only be accessed by certain people. The issue of data security and confidentiality is one of the important aspects of an information delivery system. In this case, it is closely related to how important the information is sent and received by interested people. Information will no longer be useful if in the middle of the delivery process, the information is intercepted or hijacked by unauthorized people. Computer crime is the illegal act of using knowledge of computer technology to commit a crime. Theft of hardware and software (hardware and software), manipulation of data, illegal access to computer systems by telephone, and changing programs